Cross-Species Analysis Reveals Co-Expressed Genes Regulating Antler Development in Cervidae - Ba, Hengxing; Chen, Min; Li, Chunyi (Frontiers in Genetics, 2022)
Antlers constitute an interesting model for basic research in regenerative biology. Despite decades of being studied, much is still unknown about the genes related to antler development. Here, we utilized both the genome and antlerogenic periosteum (AP) transcriptome data of four deer species to reveal antler-related genes through cross-species comparative analysis. The results showed that the global gene expression pattern matches the status of antler phenotypes, supporting the fact that the genes expressed in the AP may be related to antler phenotypes. The up-regulated genes of the AP in three antlered deer showed evidence of co-expression at gene expression level, and their protein sequences were highly conserved. These genes were growth-related, likely participate in antler development. In contrast, the up-regulated genes in antler-less deer (Chinese water deer) were involved mainly in organismal death and growth failure, possibly related to the loss of antlers during evolution. Overall, this study demonstrates that the co-expressed genes in antlered deer may regulate antler development.